Abdominal tuberculosis in children - Heda Melinda Nataprawira; Henny Komalia (Indonesian Pediatric Society, 2001)
Abdominal tuberculosis is one of the extrapulmonary tuberculosis commonly found in adolescens, however, due to its non-specific and vague abdominal symptoms, it is rarely found and reported in children. To evaluate abdominaltuberculosis in children from clinical point of view, we conducted a 5-year retrospective study on children hospitalized over a period of 1995 to 1999 in Hasan Sadikin Hospital-Bandung. Of the 15 children diagnosed as having abdominal tuberculosis, 10 (66.7%) were female and 5 (33,3%) male, age ranged from 14 – 162 months and most of them were > 10 years of age.On admission, abdominal distention was the most common complaint found (60.0%), followed by dyspnoe 3 (20.0%), abdominal pain 2 (13.3%) and generalized oedem 1 (6.7%). Most of the children (93.3%) were undernourished which half of them were severely undernourished. Seven children showed positive Mantoux testing with PPD 5 TU. There was familyhistory of adults TB discovered in 9 (60%) of the children. Eighty-percent had BCG vaccination and 6 (50%) of the showed positive scarr. Chest X-ray showed pulmonal and/or pleural involvement in 13 of the 15 children (86.7%). All ascitic fluid taken from 9 patients showed increased protein level and lymphocyte predominance. Histopathologic examinations of 5 childrensupported the diagnosis. There was no positive results of acid fast bacilli and culture done for Mycobacterium tuberculosis in gastric aspirate as well as ascitic fuid. Peritonitis tuberculosis was most commonly diagnosed (80.0%), followed by mesenterial/nodal tuberculosis (20.0%). All of the children followed (60.0%) responded well to the drugs therapy.